Aplikasi Pengorderan Gas Pada PT. XYz Berbasis Web: Gas Ordering Application at PT. XYz Web Based - Nurhayati Nurhayati; Muhammad Muhammad; Edy Wihardjo (YCMM, 2021)
This study aims to create a Gas Ordering Application at PT. xyz Web-based in helping companies to perform more efficiently and the system is easy to use by employees/accounting. The design is targeted to increase the interest of the company's performance, especially in data input and file storage. The design process takes 3 (three) months. The object of the activities carried out is in the form of interviews and direct observations in the field to see the circumstances and situations that occur, how the educational process has been going on so far. From the conditions that occur in the field in the form of recording the flow of documents, it is done by taking notes and inputting it into a computerized form in Microsoft Excel. Conclusions and suggestions on this application are in order to improve company performance and facilitate data input and file storage when doing work.